1.Rozwiąż równania.
a) 2(x-3)+3(4-x)=5
b) 3(x-4)-2(2x-5)=-4
c) 2(x+4)-5(x+3)=2
d) -2(x+3)=4(2x+3)=-6

2. Rozwiąż równania.
a) (4-2x)-(x+3)=(x-5)+(-3-x)
b) (3-2x)+(3x+4)=-(3-2x)+(5x+4)
c) -(x+3)+(2x-1)=(1+4x)+(3+x)
d) -(x+3)-(2x+8)=(-3-2x)+(2x+1)

POMÓŻCIE PROSZE !

2

Odpowiedzi

2010-02-16T18:07:21+01:00
1.Rozwiąż równania.

a)
2(x-3)+3(4-x)=5
2x-6+12-3x=5
-x=5-12+6
-x=-1/:-1
x=1

b)
3(x-4)-2(2x-5)=-4
3x-12-4x+10=-4
-x=-4-10+12
-x=-2
x=2

c)
2(x+4)-5(x+3)=2
2x+8-5x-15=2
-3x=2+15-8
-3x=12/:-3
x=-4

d)
-2(x+3)-4(2x+3)=-6
-2x-6-8x-12=-6
-10x=-6+12+6
-10x=12/:-10
x=-1,2

2. Rozwiąż równania.

a)
(4-2x)-(x+3)=(x-5)+(-3-x)
4-2x-x-3=x-5-3-x
-2x-x-x+x=-5-3+3-4
-3x=-9/:-3
x=3

b)
(3-2x)+(3x+4)=-(3-2x)+(5x+4)
3-2x+3x+4=-3+2x+5x+4
-2x+3x-2x-5x=-3+4-4-3
3x=-6/:3
x=-2

c)
-(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1=1+4x+3+x
-x+2x-4x-x=1+3+1+3
-4x=8/:-4
x=-2

d)
-(x+3)-(2x+8)=(-3-2x)+(2x+1)
-x-3-2x-8=-3-2x+2x+1
-x-2x+2x-2x=-3+1+8+3
-3x=9/:-3
x=-3
Najlepsza Odpowiedź!
2010-02-16T18:12:13+01:00
1.Rozwiąż równania.
a)
2(x-3)+3(4-x)=5
2x-6+12-3x=5
-x=5-12+6
-x=-1/:-1
x=1
b)
3(x-4)-2(2x-5)=-4
3x-12-4x+10=-4
-x=-4-10+12
-x=-2
x=2
c)
2(x+4)-5(x+3)=2
2x+8-5x-15=2
-3x=2+15-8
-3x=12/:-3
x=-4
d)
-2(x+3)-4(2x+3)=-6
-2x-6-8x-12=-6
-10x=-6+12+6
-10x=12/:-10
x=-1,2

2. Rozwiąż równania.
a)
(4-2x)-(x+3)=(x-5)+(-3-x)
4-2x-x-3=x-5-3-x
-2x-x-x+x=-5-3+3-4
-3x=-9/:-3
x=3
b)
(3-2x)+(3x+4)=-(3-2x)+(5x+4)
3-2x+3x+4=-3+2x+5x+4
-2x+3x-2x-5x=-3+4-4-3
3x=-6/:3
x=-2
c)
-(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1=1+4x+3+x
-x+2x-4x-x=1+3+1+3
-4x=8/:-4
x=-2
d)
-(x+3)-(2x+8)=(-3-2x)+(2x+1)
-x-3-2x-8=-3-2x+2x+1
-x-2x+2x-2x=-3+1+8+3
-3x=9/:-3
x=-3